Global trends and burden of idiopathic epilepsy: regional and gender differences from 1990 to 2021 and future outlook - Libo Xu; Mao Li; Zhenhao Wang; Qingsong Li (Journal of Health, Population and Nutrition)
Abstract Background Idiopathic epilepsy (IE) remains a significant neurological disorder, contributing to substantial global morbidity and mortality. This study aims to comprehensively evaluate the global burden of IE from 1990 to 2021, focusing on trends in incidence, mortality, and disability-adjusted life years (DALYs) across different geographic regions. Additionally, the study projects IE burden trends through 2036, providing insights for future public health interventions. Methods Data were extracted from the Global Burden of Disease Study 2021 (GBD 2021). IE incidence, mortality, and DALYs were analyzed by age, sex, year, and geographic location. Age-standardized rates were computed to facilitate comparisons across countries and regions. Temporal trends in IE burden were evaluated using Joinpoint regression, while future trends were projected using the Bayesian age-period-cohort (BAPC) model. Results In 2021, there were approximately 3.27 million new cases of IE globally (95% uncertainty interval [UI]: 2.4 to 4.13 million) and 140,000 deaths (95% UI: 120,000 to 150,000). Total DALYs reached 13.88 million (95% UI: 10.73 to 17.62 million). The global age-standardized incidence rate increased from 38.12 per 100,000 in 1990 to 42.82 per 100,000 in 2021. The Andean and Central Latin American regions exhibited the highest incidence rates, while East Asia and Oceania reported the lowest. Despite a decrease in the global age-standardized mortality rate from 2.07 per 100,000 in 1990 to 1.74 per 100,000 in 2021, mortality rates remained elevated in low- and middle-income countries, particularly in sub-Saharan Africa. Male patients showed consistently higher incidence, mortality, and DALY rates compared to females, with the highest burden observed in children under 5 years and adults over 60 years. Conclusion Over the past three decades, global IE incidence has steadily increased, while mortality and DALY rates have declined, especially in high-income countries. However, low- and middle-income regions continue to face significant challenges due to limited access to healthcare. Public health efforts must prioritize enhancing early diagnosis and treatment capabilities in these resource-limited areas.